2001
DOI: 10.1103/physrevlett.86.5711
|View full text |Cite
|
Sign up to set email alerts
|

Mode Selective Control of Drift Wave Turbulence

Abstract: Experiments on spatiotemporal open-loop synchronization of drift wave turbulence in a magnetized cylindrical plasma are reported. The synchronization effect is modeled by a rotating current profile with prescribed mode structure. Numerical simulations of an extended Hasegawa-Wakatani model show good agreement with experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 18 publications
7
64
1
Order By: Relevance
“…More precisely we choose a square box of 256ρ s × 256ρ s , not too close to the source region (in Fig. 1 the selected square box is between x ∈ [100, 356] in the radial direction and y ∈ [1,256] in the poloidal direction). This allows one to avoid the complex analysis of diffusive transport in finite systems, namely where the sources and sinks play an important role.…”
Section: Turbulent Potential and Test Particle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely we choose a square box of 256ρ s × 256ρ s , not too close to the source region (in Fig. 1 the selected square box is between x ∈ [100, 356] in the radial direction and y ∈ [1,256] in the poloidal direction). This allows one to avoid the complex analysis of diffusive transport in finite systems, namely where the sources and sinks play an important role.…”
Section: Turbulent Potential and Test Particle Dynamicsmentioning
confidence: 99%
“…Several experiments [1,2] have been dedicated to the control of turbulence in magnetized plasmas. Although a modelling of some of the experiments has been achieved, there was to date no theoretical backing for such a procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an advance in the study of the nonlinear interaction between drift wave turbulence and meso-scale structures such as zonal flows and streamers [1,2], and experiments in linear plasma devices have been in progress [3][4][5][6][7][8][9][10]. In these studies, complex wave patterns in poloidal direction have been observed (see also reports from toroidal plasma experiments, e.g., [11][12][13][14]).…”
Section: Introductionmentioning
confidence: 89%
“…These advancements highlight the need to measure fluctuations at multiple spatial positions simultaneously. Fluctuation measurements have been performed with poloidal multiprobe arrays in linear and toroidal plasmas [3,4,6,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the existence of zonal flows is regarded as crucial to controlling magnetically confined plasmas and realizing a thermonuclear fusion reactor [1,2]. Thus, understanding nonlinear mode coupling in drift wave fluctuation is essential [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%